Total serum FGF-21 levels positively relate to visceral adiposity differently from its functional intact form - Crudele, Lucilla; Garcia-Irigoyen, Oihane; Cariello, Marica; Piglionica, Marilidia; Scialpi, Natasha; Florio, Marilina; Piazzolla, Giuseppina; Suppressa, Patrizia; Sabbà, Carlo; Gadaleta, Raffaella Maria; Moschetta, Antonio (Frontiers in Endocrinology, 2023)
Objective: Increased Fibroblast Growth Factor-21 (FGF-21) circulating levels have been described in obesity. In this observational study, we analysed a group of subjects with metabolic disorders to unravel the putative link between visceral adiposity and FGF-21 serum levels. Methods: Total and intact serum FGF-21 concentration was measured with an ELISA assay respectively in 51 and 46 subjects, comparing FGF-21 levels in dysmetabolic conditions. We also tested Spearman’s correlations between FGF-21 serum levels and biochemical and clinical metabolic parameters. Results: FGF-21 was not significantly increased in high-risk conditions such as visceral obesity, Metabolic Syndrome, diabetes, smoking, and atherosclerosis. Waist Circumference (WC), but not BMI, positively correlated with total FGF-21 levels (r=0.31, p <0.05), while HDL-cholesterol (r=-0.29, p <0.05) and 25-OH Vitamin D (r=-0.32, p <0.05) showed a significant negative correlation with total FGF-21. ROC analysis of FGF-21 in prediction of increased WC, showed that patients with total FGF-21 level over cut-off value of 161.47 pg/mL presented with impaired FPG. Conversely, serum levels of the intact form of FGF-21 did not correlate with WC and other metabolic biomarkers. Conclusions: Our newly calculated cut-off for total FGF-21 according to visceral adiposity identified subjects with fasting hyperglycemia. However, waist circumference correlates with total FGF-21 serum levels but does not correlate with intact FGF-21, suggesting that functional FGF-21 does not necessarily relate with obesity and metabolic features.